(untitled) (Journal of Applied Learning and Teaching, 2024)
Since embarking on his educational journey in 1970, Professor Stephen Brookfield has worked across various international settings, including England, Canada, Australia, and the United States. His experience spans a diverse range of environments, from adult and community education to prestigious higher education institutions like Harvard University and Columbia University. Central to his mission is aiding adults in critically examining prevailing ideologies they have absorbed. To advance this goal, Professor Brookfield has authored, co-authored, and edited 21 books encompassing topics such as adult learning, teaching methodologies, critical thinking, discussion techniques, critical theory, and anti-racist teaching. Expanding upon our previous dialogues with Stephen Brookfield in the Journal of Applied Learning & Teaching (Brookfield et al., 2019, 2022) and complementing the reviews of his recent publications (Rudolph, 2019, 2020, 2022; Waring, 2024), this interview delves deeper into the themes explored in our recent book on Teaching well (Brookfield et al., 2024). This extensive conversation significantly elaborates on Chapter 9 of the book (Brookfield et al., 2024) and investigates the intricate, emotionally charged, and political project of teaching about race. In this expansive discussion, we explore Stephen Brookfield’s personal evolution from harbouring racist beliefs in his youth to embracing and contributing to Critical Race Theory (CRT), a journey marked by a decade of introspection and scholarly exploration, culminating in several key publications (Sheared et al., 2010; Brookfield & Associates, 2018; Brookfield & Hess, 2021). The conversation illuminates fundamental concepts such as race, racism, and white supremacy, recontextualising racism as a systemic issue rather than an individual failing. Racism is depersonalised and an endemic system of exclusion. We discuss it in the context of an intersectional analysis that acknowledges the interconnectedness of various forms of oppression, including classism, sexism, and ableism. A significant focus is placed on racism within the higher education sector. Brookfield shares insights from his extensive experience in conducting antiracist workshops for students, faculty, and organisations. He challenges the notion of the ‘good white people’ and advocates for a continuous, imperfect journey towards antiracism, where ‘failing well’ can be regarded as a good outcome.